Phosphorus Management in High‐Yield Systems. Issue 5 (12th September 2019) - Hopkins, Bryan G.; Hansen, Neil C.
Abstract : The discovery and development of phosphorus (P) and P fertilizers provide context for current management conventions. Average crop yields were stagnant before the Green Revolution but have steadily increased since. This, along with conventional P management, has resulted in widely depleting soil P levels. Improved technology and management are needed to meet the increasing P demand. Modern hybrids and cultivars have different P demand and uptake patterns that require changes in conventional P fertilizer placement and timing. Phosphorus fertilizer recommendations based on soil analysis remains valid, but evidence suggests a need for recalibrating soil test P (STP) critical levels (the STP concentration at which a response to P fertilizer would not be expected) and P fertilizer rates to accommodate high‐yield scenarios. Considering higher P fertilizer rates as a single solution poses environmental challenges, highlighting the need for improved P use efficiency (PUE). Phosphorus fertilization approaches that have the potential to improve PUE and enable high yields include crop‐specific precision placement of P, informed timing of P fertilizers, and new enhanced efficiency sources of P fertilizer. This paper examines these management approaches from historical, production, and environmental perspectives in modern cropping systems. Core Ideas: History of P fertilization illuminates traditional soil P management and needed changes. Recalibration of STP and P fertilizer recommendations are needed to match increasing yield and rates of P uptake. Environmental concerns and diminishing P supply necessitate improvement in P use efficiency. Placement and timing are improved through understanding of variable rooting patterns. Enhanced efficiency P fertilizers can be effective if applied correctly.